Invasive meningococcal disease in elderly people, New South Wales, Australia, 1993 to 2012 - Praveena Gunaratnam; Peter Massey; David Durrheim; Siranda Torvaldsen (World Health Organization Regional Office for the Western Pacific, 2013)
Little information is available publicly on invasive meningococcal disease (IMD) in elderly people in Australia. This study analysed IMD notifications data from New South Wales between 1993 and 2012 to determine the distribution of IMD among people aged 65 years and older and to describe the characteristics of IMD in this age group compared to younger age groups with respect to notification trends, serogroup distribution and mortality rates. Following introduction of a childhood vaccination programme against meningococcal type C in 2003, notification rates in all age groups decreased, but the proportion of IMD notifications in people aged 65 years and over rose significantly (from 4% to 6%, P = 0.01). Mortality rates from IMD in those aged 65 years and older were significantly higher than overall rates (32% compared to 5%, P < 0.01). Serogroup Y accounted for 23% of infections in the elderly compared to 3% in people aged under 65 years (P < 0.01). As the population ages, the elderly may account for a higher number of IMD cases in Australia. Protocols at the state and national level should be updated to provide guidance on the clinical and public health management of elderly people with IMD.